Drainage network analysis to comprehend structural sediment (dis)connectivity in wine-growing Beaujolais (France). Issue 27 (13th December 2022) - Pic, Jessica; Cossart, Étienne; Fressard, Mathieu; Carluer, Nadia
Abstract: Drainage infrastructure is an important element of the agricultural landscape, influencing hydro-sedimentary transfers from plots to rivers. The objective of this article is to demonstrate how the description of the main characteristics of drainage networks allows a better understanding of sediment (dis)connectivity. This study focuses on an 8 km 2 catchment in the Beaujolais vineyards (France) that is characterized by a complex drainage network. We applied methods using field surveys, a geographical information system and graph theory to map and analyse how such man-made infrastructures may act as barriers, buffers or shortcuts. The catchment shows dense and complex drainage networks characterized by sediment trapping strategies in the upper slopes, and flow concentration and export in the lower slopes. The results exemplify winegrowers' strategies to disconnect sediments sources from the river to preserve soil resources.